Entrepreneurial competencies and microenterprises sustainability - Al Mamun, Abdullah; Fazal, Syed Ali; Ahmad, Ghazali; Al-Shami, Sayed Samer Ali (SAGE Publications Ltd, 2022)
In this article, we report a study undertaken to measure the effects of selected competency dimensions on the microenterprise sustainability in Malaysia under the premise of the resource-based view (RBV). We adopted a cross sectional approach. Quantitative data were collected from 300 micro-entrepreneurs in Malaysia who were selected using a random sampling technique. Commitment, conceptual, opportunity recognizing, organizing and relationship competencies had significant positive impacts on microenterprise sustainability. The empirical evidence forwarded in this article extends the current micro-entrepreneurship literature in Malaysia and recommends that relevant policy measures need to be enforced for improving microenterprise sustainability based on key entrepreneurial competencies.